2014
DOI: 10.3892/ijmm.2014.1786
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and gastrointestinal diseases: The causal relationship and underlying molecular mechanisms (Review)

Abstract: Cigarette smoking is an important risk factor for gastrointestinal (GI) disorders, including peptic ulcers, inflammatory bowel diseases, such as Crohn's disease and cancer. In this review, the relationship between smoking and GI disorders and the underlying mechanisms are discussed. It has been demonstrated that cigarette smoking is positively associated with the pathogenesis of peptic ulcers and the delay of ulcer healing. Mechanistic studies have shown that cigarette smoke and its active ingredients can caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(123 citation statements)
references
References 102 publications
2
111
3
7
Order By: Relevance
“…Several studies have shown that cigarette smoke and its active ingredients can cause mucosal cell death, inhibit cell renewal, decrease blood flow in the gastrointestinal mucosa, and interfere with the mucosal immune system. (15,16) The present study shows that, the majority of studied male patients (57 out of 78 or 73%) reported that they were smokers. Similar findings were reported by Chen et al, who supposed a strong association between cigarette smoking & stimulants (coffee) and prevalence of DUs, and this prevalence increase linearly with an increase in the number of cigarettes smoked, irrespective of the duration of smoking and increased with an increase in the number of cups of coffee ingested daily (17) .…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have shown that cigarette smoke and its active ingredients can cause mucosal cell death, inhibit cell renewal, decrease blood flow in the gastrointestinal mucosa, and interfere with the mucosal immune system. (15,16) The present study shows that, the majority of studied male patients (57 out of 78 or 73%) reported that they were smokers. Similar findings were reported by Chen et al, who supposed a strong association between cigarette smoking & stimulants (coffee) and prevalence of DUs, and this prevalence increase linearly with an increase in the number of cigarettes smoked, irrespective of the duration of smoking and increased with an increase in the number of cups of coffee ingested daily (17) .…”
Section: Discussionmentioning
confidence: 87%
“…With a percentage of 18.8% of alcohol consumers, our study also identified alcohol use as a risk factor for ulcer on endoscopy, using multiple logistic regressions (OR = 3.0, 95% CI: 1.2–7.4). Despite the proven role of smoking in the pathogenic mechanism of peptic ulcer [34] that may be synergistic with LDA mucosal aggression and H. pylori inflammation, smoking was not a predictor for ulcer in our group, as in other published studies [7]. Alcohol consumption and smoking, although involved in the pathogenesis and progression of many diseases, did not have a predictive role for ulcer in our final model study after adjustment for the presence of comorbidities or concomitant gastrotoxic drug consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicated that smoking had adverse effects on human health and represented a predisposing factor for development of various pathological conditions and diseases, such as the chronic obstructive pulmonary disease (1), cancer (2), pancreatitis (3), gastrointestinal disorders (4), periodontal disease (5), metabolic syndrome (6), and some autoimmune diseases (7). …”
Section: Introductionmentioning
confidence: 99%